2017
DOI: 10.1139/apnm-2016-0201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous vitamins A, C, and E and NADH supplementation on proliferation, cytokines release, and cell redox status of lymphocytes from healthy aged subjects

Abstract: Aging is an inevitable biological event that is associated with immune alterations. These alterations are related to increased cellular oxidative stress and micronutrient deficiency. Antioxidant supplementation could improve these age-related abnormalities. The aim of this study was to determine in vitro effects of vitamin A, vitamin C, vitamin E, and nicotinamide adenine dinucleotide (NADH) on T cell proliferation, cytokine release, and cell redox status in the elderly compared with young adults. Peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 77 publications
0
19
0
1
Order By: Relevance
“…Furthermore, undernourishment has been well shown to be associated with impairment of immune function of the host . Some micronutrients are possibly of importance in protecting against reactivated TB, through anti‐oxidative and other mechanisms . Interestingly, obesity appears to protect against development of TB .…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, undernourishment has been well shown to be associated with impairment of immune function of the host . Some micronutrients are possibly of importance in protecting against reactivated TB, through anti‐oxidative and other mechanisms . Interestingly, obesity appears to protect against development of TB .…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
“…83 Some micronutrients are possibly of importance in protecting against reactivated TB, through anti-oxidative and other mechanisms. 84,85 Interestingly, obesity appears to protect against development of TB. 86 The relevance of nutritional attention in preventing and managing TB is likely to be highest in geriatric patients, and more research appears warranted.…”
Section: Future Research Directions Regarding Tb In Older Peoplementioning
confidence: 99%
“…6 VC at high concentrations reduces the viability of lymphocytes and inhibits lymphocyte proliferation in vitro, [7][8][9] while optimal concentrations of VC promote B-cell proliferation in response to LPS 8 and T-cell proliferation in response to the mitogen concanavalin A. 10 VC also augments the in vitro proliferative capacity of human NK cells. 11 Furthermore, it has been reported that VC increases the stability and function of regulatory T cells through Tet-dependent demethylation of the FoxP3 regulatory elements.…”
Section: Introductionmentioning
confidence: 99%
“…Using some injectable vitamins such as vitamin C and oral vitamin E, vitamin D and multivitamin and highly effective antioxidant drugs such as immunace syrup under the supervision of doctors are effective. So according to this study consumption of the above mentioned treatments and prevention of coronavirus disease are recommended [6,7,13,14].…”
Section: Theory About Treatments and Morbidity Prevention Of Corona Vmentioning
confidence: 99%